1999
DOI: 10.1038/sj.onc.1202371
|View full text |Cite
|
Sign up to set email alerts
|

Multiple target sites of allelic imbalance on chromosome 17 in Barrett's oesophageal cancer

Abstract: Twelve Barrett's adenocarcinomas have been analysed for the occurrence of allelic imbalance (LOH) on chromosome 17 using 41 microsatellite markers. This study provides evidence for 13 minimal regions of LOH, six on 17p and seven on 17q. Four of these centre in the vicinity of the known tumour suppressor genes (TSGs) TP 53 (17p13.1), NF1 (17q11.2), BRCA1 (17q21.1), and a putative TSG (17p13.3). The tumours all displayed relatively small regions of LOH (1 ± 10 cM), and in several tumours extensive regions of LOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Our previous studies based on allelic imbalance data suggest the presence of a human Barrett's oesophageal adenocarcinoma (BOA) tumour suppressor gene (TSG) in a minimally deleted region of chromosome 17p (C17p) centromeric to the p53 TSG (Dunn et al, 1999(Dunn et al, , 2000, and multiplex PCR has confirmed that the allelic imbalance in this region is because of loss of heterozygosity (LOH) rather than amplification of the region (Dunn, unpublished). In this study, we have assembled physical and transcript maps of the deleted region (minimal region III-'MRIII') from which the candidate BOA TSG can be identified.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies based on allelic imbalance data suggest the presence of a human Barrett's oesophageal adenocarcinoma (BOA) tumour suppressor gene (TSG) in a minimally deleted region of chromosome 17p (C17p) centromeric to the p53 TSG (Dunn et al, 1999(Dunn et al, , 2000, and multiplex PCR has confirmed that the allelic imbalance in this region is because of loss of heterozygosity (LOH) rather than amplification of the region (Dunn, unpublished). In this study, we have assembled physical and transcript maps of the deleted region (minimal region III-'MRIII') from which the candidate BOA TSG can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…By using 10 pairs of normal/tumour samples for the SSCP analysis, it was assumed that any causative mutations would be identified. This is because the overall frequency of LOH at MRIII in our earlier study was 75% and, in addition, we have found LOH at MRIII in Barrett's intestinal metaplasia in 4/5 samples tested (Dunn et al, 1999(Dunn et al, , 2000. The two tumours used in the sequence analysis of x006 were selected because they were the most likely tumours to show a mutation, since they only showed LOH at MRIII (i.e.…”
Section: Mutation and Expression Analysis Of Magoh-like And X006mentioning
confidence: 99%
See 3 more Smart Citations